Supplement of secreted recombinant low molecular weight human fibroblast growth factor 2 in culture media enhances in vitro bovine maturation. (31st December 2022) - Kim, Min-Ji; Gim, Gyeong-Min; Jang, Goo
Abstract: With the annual increase in in vitro bovine embryo production, understanding oocyte maturation is becoming more important. Previous studies have shown that oocyte maturation can be improved by adding bovine additives to in vitro maturation media. Among the additives, human fibroblast growth factor 2 (hFGF2) is well known for its positive influence on the growth rate and quality of cells and oocytes. However, the effect of LMW-hFGF2, one of the isoforms of hFGF2, on bovine in vitro maturation has not yet been identified. Therefore, the goal of this study was to elucidate the effect of LMW-hFGF2 on bovine oocyte maturation. Vectors expressing LMW-hFGF2 were cloned and transfected into cells. Afterward, secretion of LMW-hFGF2 from cells was confirmed, and used to assess the effect LMW-hFGF2 on cells and bovine oocytes. LMW-hFGF2 improved bovine oocyte maturation and embryo developmental competence. Laboratories can use LMW-hFGF2 in bovine oocyte culture media to improve in vitro embryo production success rates. Highlights: LMW-hFGF2 could extracted from recombinant cell culture media. Recombinant LMW-hFGF2 could improve the cell proliferation on immortalized and primary cell lines. Supplement of LMW-hFGF2 to IVM media could improve bovine oocyte maturation. LMW-hFGF2 could improve bovine embryo development competency both on parthenogenesis and in vitro fertilization.